Implementasi Kegiatan Bermain Outdoor Dalam Mengembangkan Motorik Kasar Di Tk Pkk Banjarjo Pudak Ponorogo - Ririn, Ririn; Hijriyani, Yuli Salis (Institut Agama Islam Negeri Ponorogo, 2020)
Abstract: Physical-motor development is physical development through coordinated nerve center, nerve, and muscle activities. Before the development of motor movement begins to process, then the child will remain helpless. The objectives of this study are: 1) The forms of outdoor play activities in TK PKK Banjarjo Pudak Ponorogo. 2) Implementation of outdoor play activities in developing gross motor skills in TK PKK Banjarjo Pudak Ponorogo. 3) Supporting and inhibiting factors in implementing outdoor play activities to develop gross motor skills in PKK Banjarjo Kindergarten, Pudak Ponorogo. The research approach used is qualitative research with a type of case study research. Data collection techniques in this study used observation, interview, and documentation techniques. The data analysis technique follows the concepts put forward by Miles and Huberman namely data reduction, data presentation, and conclusion drawing. From the analysis of the data it was concluded that: 1) The forms of outdoor play activities included playing outside APE such as seesaw, globe and swing, gymnastics using music, playing traditional games such as crickets, stilts and snakes, observing plants and imitating animal paths. 2) Implementation of outdoor play activities in developing gross motor skills by exercising using music every day if the yard is not wet and playing outside APE such as seesaw, globe and swing every day at rest.3) Supporting factors in implementing outdoor play activities to develop gross motor skills that is the enthusiasm of children participating in learning with enthusiasm, besides that the motivation of school principals and teacher cohesiveness to achieve common goals while the inhibiting factor in implementing outdoor play activities to develop gross motor skills is the inadequate funding and yard factors.